Curriculum 2013: Analysis of biology teachers’ obstacles in senior high schools, Sungai Kanan district - Fitri Andreani; Rahmi Nazliah (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
This study aims to explore the obstacles of biology teachers in Sungai Kanan senior high schools have in implementing the curriculum 2013. In this qualitative study, biology teachers in high schools in the Sungai Kanan District served as the subjects. The population utilized is comprised of high school teachers from the Sungai Kanan District, including six individuals from SMAN 1 Sei Kanan, SMAN 2 Sei Kanan, and SMAS Karya Handayani. The approach employed is purposive sampling, questionnaires and interviews are utilized to obtain data. According to the findings of an examination of the hurdles biology instructors face in adopting the 2013 curriculum, which has been in place for about eight years, senior high school biology teachers in the Sungai Kanan subdistrict have no obstacles to implementing the 2013 curriculum. Biology teachers' comprehension of the indicators of biology teachers' comprehension in the 2013 curriculum; biology teachers' comprehension of the 2013 syllabus; biology teachers' comprehension of the 2013 lesson plans; biology teachers' comprehension of the biology lesson process; biology teachers' comprehension of the 2013 curriculum's facilities and infrastructure; and biology teachers' comprehension of the biology lesson process This problem is caused by the fact that the 2013 biology teacher's manual was not finished yet, lack of time, teachers and students, infrastructure, and supportive facilities.